Subjective Symptoms in Magnetic Resonance Imaging Personnel: A Multi-Center Study in Italy - Bravo, Giulia; Modenese, Alberto; Arcangeli, Giulio; Bertoldi, Chiara; Camisa, Vincenzo; Corona, Gianluca; Giglioli, Senio; Ligabue, Guido; Moccaldi, Roberto; Mucci, Nicola; Muscatello, Martina; Venturelli, Irene; et al. (Frontiers in Public Health, 2021)
Introduction: Magnetic Resonance Imaging (MRI) personnel have significant exposure to static and low-frequency time-varying magnetic fields. In these workers an increased prevalence of different subjective symptoms has been observed. The aim of our study was to investigate the prevalence of non-specific subjective symptoms and of “core symptoms” in a group of MRI personnel working in different centers in Italy, and of possible relationships with personal and occupational characteristics. Methods: The occurrence of 11 subjective symptoms was evaluated using a specific questionnaire with 240 subjects working in 6 different Italian hospitals and research centers, 177 MRI health care and research personnel and 63 unexposed subjects employed in the same departments. Exposure was subjectively investigated according to the type of MRI scanner (≤1.5 vs. ≥3 T) and to the number of MRI procedures attended and/or performed by the personnel, even if no information on how frequently the personnel entered the scanner room was collected. The possible associations among symptoms and estimated EMF exposure, the main characteristics of the population, and job stress perception were analyzed. Results: Eighty-six percent of the personnel reported at least one symptom; drowsiness, headache, and sleep disorders were the most frequent. The total number of symptoms did not differ between exposed persons and controls. Considering the total number of annual MRI procedures reported by the personnel, no significant associations were found nor with the total number of symptoms, nor with “core symptoms.” Only subjects complaining of drowsiness also reported a significantly higher mean annual number of MRI procedures with ≤ 1.5 T scanners when compared with exposed subjects without drowsiness. In a multivariate model, subjects with a high level of perceived stress complained of more symptoms (p = 0.0002). Conclusions: Our study did not show any association between the occurrence of reversible subjective symptoms, including the more specific “core symptoms,” and the occupational exposure of MRI personnel to static and low-frequency time-varying magnetic fields. On the other hand, the role played by occupational stress appears to be not negligible. In further research in this field, measurements of EMF exposure should be considered.